Learning Angular Services - Orgill, Sam (Packt, 2019)
"Angular services hold the business logic of an application and are used to organize and share code between components through dependency injection. With this course, you'll get answers to all Angular Services use cases, and more. We will start to make use of existing services and tackle different Angular challenges. So, let's build our own custom Angular services and master the concept of Observables. Each section of this course provides you with hands-on training in working with custom services or built-in services. This course will teach you not only to build services but also to use them in Angular components. By the end of this course, you will be able to create dynamic web applications using the REST API, unit-test your services, and develop a more solid understanding of asynchronous and reactive programming."--Resource description page